2019
DOI: 10.1016/j.matpur.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Convolution semigroups on locally compact quantum groups and noncommutative Dirichlet forms

Abstract: The subject of this paper is the study of convolution semigroups of states on a locally compact quantum group, generalising classical families of distributions of a Lévy process on a locally compact group. In particular a definitive one-to-one correspondence between symmetric convolution semigroups of states and noncommutative Dirichlet forms satisfying the natural translation invariance property is established, extending earlier partial results and providing a powerful tool to analyse such semigroups. This is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…We need a slightly more general version going beyond the case of tracial states of their construction. Note that we do not prove the existence of a square root in the non-tracial setting however (which is one of the main results of [21]; the question is also asked for in [60]).…”
Section: Gradient Forms and The Results By Cipriani-sauvageotmentioning
confidence: 72%
See 1 more Smart Citation
“…We need a slightly more general version going beyond the case of tracial states of their construction. Note that we do not prove the existence of a square root in the non-tracial setting however (which is one of the main results of [21]; the question is also asked for in [60]).…”
Section: Gradient Forms and The Results By Cipriani-sauvageotmentioning
confidence: 72%
“…their generators) to obtain strong solidity for all free orthogonal and unitary quantum groups. Dirichlet forms have been studied extensively [18,[20][21][22]29,35,58,60]. In particular in [21] it was shown that in the tracial case a Dirichlet form always leads to a derivation as a square root.…”
Section: Introductionmentioning
confidence: 99%
“…Only the relevant parts are stated; for the rest, see [SkV]. We take the opportunity to fix a mistake in the statement of [SkV,Theorem 0.1]: the words 'modulo multiplication of forms by a positive number' should have been 'modulo subtracting a positive multiple of the quadratic form • 2 ', see Remark 1.5.…”
Section: Preliminariesmentioning
confidence: 99%
“…(2,ϕ) µt for all t ≥ 0 ((a)⇔(b)) and the general correspondence between selfadjoint completely Markov semigroups and completely Dirichlet forms [SkV,Corollary A.8] ((b)⇔(c)); the latter means that (S t ) t≥0 = (e −tA ) t≥0 , where A is the positive selfadjoint operator on L 2 (G) such that Q = A 1/2 • 2 . Remark 1.5.…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation